Peningkatan Literasi Keuangan, Efikasi Diri, dan Perilaku Kredit Berisiko melalui Workshop Smart Money Management bagi Mahasiswa Kirirom Institute of Technology, Cambodia - Imelda Junita; Maya Malinda; Johannes Buntoro Dharmasetiawan; Joni Joni; Meythi; Riki Martusa; Santy Setiawan; Rapina; Tan Ming Kuang; Surya Setyawan (Jurnal Atma Inovasia, 2025)
The Smart Money Management community service program was designed to improve financial literacy, self-efficacy, and reduce risky credit behavior among students at Kirirom Institute of Technology (KIT), Cambodia. In the context of students facing challenges in personal financial management due to lack of knowledge and experience, this program aims to equip them with basic knowledge of financial management through an educational and interactive approach. The implementation method includes delivering materials on the concepts of SMART Goal and Smart Money Management, as well as participatory training activities in the form of frugal living action pictures. The evaluation results showed that the financial literacy score increased from 2.37 to 2.57, and self-efficacy from 3.28 to 3.7, while the perception of risky credit behavior decreased by 0.08 points. In addition, the results of the personal assessment showed an increase in the number of students who had a high understanding of finance from 2 to 7 people. These findings indicate that the program was successful in improving participants' understanding and positive attitudes towards financial management. Thus, this program contributes to strengthening students' ability to make wise financial decisions and fostering a disciplined and independent attitude in managing their finances in the future.